correlation between life style and gingival health in adult patients in Erbil city-Iraq - Shahida Rassul Hussein (Polytechnic Journal)
ABSTRACT Back ground and Objective: Gingivitis conceder as one of the most common, gum diseases. lifestyle choices can related to gingivitis such as diet, oral hygiene practices, regular dental visits and smoking . The objective of this study was to determine the relationship between life style and gingivitis of adult population in Erbil city. Methods: effect of life style on gingival health was determined for 360 patients age between 20-70years of both genders, visiting Erbil medical centers. Clinical examination of the gingival health was performed by reporting plaque, gingival indices by periodontal prob. Lifestyle was detected by questions about dietary habits, smoking habits, and physical activity ,frequency of tooth brushing were also recorded . Results: Demonstrated that ; the highest mean for plaque(.857) ,gingival (.942) scores were increased with increasing vegetable taking per week with statistical significant differences for plaque score (P-value =0.000) and gingival score (P-value =0.000) while mean plaque(.563 )score gingival(.663) score were decrease with increasing fruit taking per week with statistical significant differences for plaque (P-value =0.000) and gingival score (P-value =0.000) . higher means of plaque(1.145) and gingival(1. 000) scores were reported among individuals who were take 0-1 times per week of egg and butter with statistical highly significant differences between all for plaque and gingival indices (P-value =0.000) . The highest mean of plaque (1.109), gingival (1.04) scores were seen related to 0-1 time per week of meat taking with highly statistical significant difference between groups (P-value =0.000). The highest mean of plaque (.745) were reported among non smoker groups with statistically no significant difference (P-value =0.149) and gingival (.790) scores, were seen related to heavy smoker groups with significant differences between both groups. (P-value =0.041). The lowest mean of plaque (.630) and gingival (.629) scores were among persons who performing daily exercise with statistical significant differences (P-value =0.069) (P-value =0.049) for plaque and gingival indices respectively. The lowest mean of plaque (.518) and gingival (.588) scores were reported among individuals with regular daily tooth brushing with statistical significant differences (P-value =0.011) for plaque index and highly significant differences for gingival index (P-value =0.001). Conclusions: There was a positive correlation between life style and gingival health.